Uji Empiris Nisbah Keuangan Leverage, Indebtedness dan Produktivitas sebagai Pembeda Pertumbuhan Earning di Masa Krisis - Mahadwartha, Putu Anom (Jurnal Widya Manajemen & Akuntansi, 2002)
The research focused on the investigation of two variables: interest rate cost and sales, one of them is able to differentiate positive and negative earnings among firms. Sales level proxies by productivity ratio and interest rate cost proxies by leverage and indebtedness ratio. Discriminant analysis was used and the result supported the null hypothesis that indebtedness ratio (proxy for interest rate cost) dominantly differentiates firm with positive earnings from firms with negative earnings in the period of crisis.